Efficient Power Flow Algorithm for Unbalanced Three-Phase Distribution Networks using Recursion and Parallel Programming - De Souza, Mariana; Leite, Jonatas B. [UNESP]; Reiz, Cleberton (Institute of Electrical and Electronics Engineers (IEEE), 2024)
In this work, the implementation of an efficient multi-threading algorithm for calculating the power flow in electricity distribution networks is carried out using recursion and parallel programming. With the integration of renewable energy, energy storage systems and distributed generation, the ability of power flow simulations becomes a crucial factor in finding the best solution in the shortest possible time. We propose the direct use of graph theory to represent distribution network topologies. In this data structure, the traversal algorithms are inherently recursive, thus enabling the development of algorithms with parallel programming to obtain the power flow calculation faster and more efficiently. Results under a 809 buses test system show that the implementation provides additional computation efficiency of 32% with recursion techniques and 27% with parallel programming, due the expense of threads' allocation the combined gain reaches 50%.
Keywords: Distribution Network; Graph Theory; Parallel Programming; Power Flow; Recursion